Suplementação de alto consumo para bovinos de corte em pastejo - Botini, Leonardo Antonio (2018)
Two experiments were carried out to evaluate the nutritional parameters of grazing cattle receiving high intake supplements. In experiment 1 the objective was to evaluate the substitution of ground corn (GC) per whole corn grain (WCG) on nutritional parameters of beef cattle grazing Marandu grass during the rainy-dry transition period. To evaluate ruminal parameters, five dairy crossbreeds steers, non‑fistulated, were used, with average initial body weight (BW) of 430,0±9,56, allotted to a 5x5 Latin square. Were evaluated supplements (19,77% CP) with 0, 25; 50;, 75 and 100% of WCG in substitution of GC provided in the amount of4,5 kg/animal daily. There was no effect on the intakes of total dry matter (TDM), pasture dry matter (pDM), as well as for organic matter (OM), crude protein (CP), ethereal extract (EE), neutral detergent fiber corrected for ashes and protein (NDFap), non-fibrous carbohydrates (NFC) and total digestible nutrients (TDN). The apparent digestibilities means of dry matter (DM), OM, CP, NDFap and NFC had no effect as to the substitution of GC to WCG. The rumen pH, the ruminal NH3 concentration and the N-serum were not influenced by the substitution levels. There was no effect on parameters related to intake, excretion and retention of nitrogen, as well as in the efficiency of nitrogen utilization. WCG can be used in total substitution to GC in high concentrate supplements to grazing beef cattle without harm on intake and digestibilities of diet nutrients. In experiment 2 the objective was to evaluate crude protein levels on nutritional parameters of beef cattle grazing Marandu grass during dry season. To evaluate ruminal parameters, five non‑fistulated, dairy crossbreeds steers were used, with average initial body weight (BW) of 466,8±18,4 kg, allotted to a 5x5 Latin square. Were evaluated supplements with 10, 12,5 15, 17,5 and 20% of crude protein provided in the amount of 2% of BW. Intakes of TDM, pasture DM, OM and NDFap presented quadratic behavior, with higher consumption at the level of 17.5% of CP in the supplement. The apparent digestibility of DM, OM, and NDFap also showed quadratic behavior with higher digestibility being noticed at the level of 17.5% of CP in the supplement. Rumen pH was not influenced and the concentrations of ruminal NH3 and serum nitrogen had a linear increase. The nitrogen intake, urinary and feces nitrogen excretions, increased positively with higher CP levels. High intake supplements (2% of BW) offered to grazing cattle during dry season must contain 17,5% of CP to maximize forage utilization.